Working in home healthcare and suggestions for development. Issue 4 (2nd October 2019) - Vaartio-Rajalin, Heli; Näsman, Yvonne; Santamäki-Fischer, Regina; Hemberg, Jessica
ABSTRACT: In order to describe nurses' experiences of working in home health care and their suggestions for the development of this public health-care sector, interviews with 18 home health-care nurses were analyzed with qualitative thematic content analysis. The nurses perceived the working shifts either affirmative or non-affirmative, depending on the contextual and organizational factors affecting nurses' workload. The more the nurses perceived they could influence their work, the more engaged they were in patient-related nursing activities, patient-centeredness, collaboration, and forward planning. Several concrete suggestions for the development of home healthcare on the organizational, interprofessional, team and individual levels were given.